Olhar a cidade: (re)descobertas perceptivas espaciais - Silva, Naiara Bettiato Pasquale da (Universidade do Vale do Rio dos Sinos, 2017)
This research has as its theme the analysis of the elements that compose the public spaces of the city, such as sidewalks, green areas and buildings, among others, from the point of view of the visual perception as much of the other senses - sensibility - of the people who circulate by these spaces. The objective is to propose a qualitative analysis instrument capable of evaluating public spaces in order to recognize and list the main elements that influence the interrelationship of people and the quality of public spaces. In this aspect, perceptual variables are analyzed in the research, linked to socio-spatial interaction, technology and information, culture and landscape forms, so that it is possible to apply a perceptual map from local images, evaluated by users in segments of around the Rua dos Andradas, Av. Independência and Rua 24 de Outubro in the city of Porto Alegre (RS), taken as a case study. Through data collection, it was possible to identify a set of attributes - comfort, diversity of uses, (in) safety, movement of people and arrangement of green areas - that attract different groups of people. The results obtained reinforce the importance of these public spaces as a way of passages and stays that, qualified, rescue the living and the inclusion of all the people, besides stimulating their displacement and well-being, as a way to improve the structure of spaces Public, then (re) discover the city.
Keywords: Pessoas; Espaços públicos; Cidade; Percepção espacial; Sensibilidade; People; Public spaces; City; Spatial perception; Sensitivity; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo